Oil Price Uncertainty and IPOs - Blomkvist, Magnus; Dimic, Nebojsa; Vulanovic, Milos (International Association for Energy Economics, 2023)
We examine the impact of oil price uncertainty on IPO volume in the oil and gas sector. By using the implied volatility of oil options, a forward-looking uncertainty measure, we identify the effect of uncertainty on the going-public decision. Oil price uncertainty exhibits a strong negative relation to IPO volume. A one standard deviation decrease in the implied volatility results in a 29% increase in the number of quarterly IPOs. The effect is concentrated among the price-sensitive upstream producers. We further report that uncertainty positively impacts the IPO withdrawal decision and increases the value of postponing the offering.
Keywords: Energy economics; IPOs; Implied crude oil volatility; Oil and gas sector; Oil price uncertainty; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|